2022
DOI: 10.1002/pul2.12034
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effects of sacubitril/valsartan versus enalapril on pulmonary hypertension due to heart failure with a reduced ejection fraction

Abstract: The purpose of this study was to investigate the effects of sacubitril/valsartan on right ventricular (RV) function in patients with pulmonary hypertension (PH) due to heart failure with reduced ejection fraction (HFrEF). We prospectively enrolled patients with HFrEF‐induced PH admitted to the Department of Cardiology between August 2018 and December 2019. Patients were randomized to receive oral treatment with sacubitril/valsartan or enalapril. Epidemiological data were recorded before treatment. Echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Invasive measurement also revealed a significantly reduced mean PCW at follow-up in patients with IpcPH [18 (15-23) mm Hg vs. 21 (18)(19)(20)(21)(22)(23)(24)(25)(26) mm Hg presacubitril/ valsartan, P , 0.01] (Fig. 1), whereas the reduction in mean PCW in patients with CpcPH was only tendential but not statistically significant [16 (10-25) mm Hg vs. 21 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) mm Hg presacubitril/valsartan, P = 0.09] (Fig. 2).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Invasive measurement also revealed a significantly reduced mean PCW at follow-up in patients with IpcPH [18 (15-23) mm Hg vs. 21 (18)(19)(20)(21)(22)(23)(24)(25)(26) mm Hg presacubitril/ valsartan, P , 0.01] (Fig. 1), whereas the reduction in mean PCW in patients with CpcPH was only tendential but not statistically significant [16 (10-25) mm Hg vs. 21 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) mm Hg presacubitril/valsartan, P = 0.09] (Fig. 2).…”
Section: Resultsmentioning
confidence: 94%
“…[12][13][14] Other studies have shown that sacubitril/valsartan reduces pulmonary pressure and improves right ventricular function in patients with heart failure with reduced ejection fraction, which does not seem to depend on reverse of left ventricular remodeling. [15][16][17][18] More recently, 2 small case series have shown that sacubitril/ valsartan also affects PAP in patients with HFpEF, suggesting an effect of sacubitril/valsartan on pulmonary hypertension independent of left ventricular function. 19,20 Therefore, we sought to investigate whether sacubitril/ valsartan affects pulmonary hypertension in a larger cohort of symptomatic patients with HFpEF.…”
Section: Introductionmentioning
confidence: 99%